2022
DOI: 10.3390/diagnostics12081967
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Hypertension and Diabetes Mellitus Using Korean Public Health Examination Data (2002–2017)

Abstract: Hypertension and diabetes mellitus are major chronic diseases that are important factors in the management of cardiovascular disease. In order to prevent the occurrence of chronic diseases, proper health management through periodic health check-ups is necessary. The purpose of this study is to determine the incidence of hypertension and diabetes mellitus according to the health check-up, and to develop a predictive model for hypertension and diabetes according to the health check-up. We used the National Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Studies that developed diabetes prediction models using health checkup data generally did not consider 2-hour glucose when defining diabetes. 25 26 However, in line with previous studies, 27 28 we observed differences in prevalence depending on the definition of diabetes. Also, one meta-study suggested lowering the cutoff values for FBG and HbA1c in relation to diabetes diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Studies that developed diabetes prediction models using health checkup data generally did not consider 2-hour glucose when defining diabetes. 25 26 However, in line with previous studies, 27 28 we observed differences in prevalence depending on the definition of diabetes. Also, one meta-study suggested lowering the cutoff values for FBG and HbA1c in relation to diabetes diagnosis.…”
Section: Discussionsupporting
confidence: 90%